Pengembangan Transportasi Berkelanjutan untuk Mewujudkan Konsep TOD sebagai Pengentas Permasalahan Perkotaan di Kota Surabaya - Fatmawati, Yumnaa Giri (Mahesa Research Center, 2022)
This article aims to analyse the development of sustainable transportation in the city of Surabaya which has the potential to realise the concept of Transit Oriented Development (TOD) as a solution to urban problems in the city of Surabaya. The problem is focused on the analysis of Sustainable Transportation and the concept of TOD in the city of Surabaya. To approach this problem, theoretical references from the Organization Of Economic Transportation (1996) and National Round Table On The Environment And The Economy (1996) are used to describe the related sustainable transportation and the theory of Peter Calthrope (1993) which describes the concept of TOD. Primary data was obtained from observation and secondary surveys, while secondary data was obtained through literature analysis. The data analysis approach was carried out using qualitative methods with a level of focus on deepening descriptive analysis. The results of the study state that the Surabaya City Government needs to develop the availability of sustainable transportation that is already available and careful development planning in transit areas that already have the potential to realise the application of the TOD concept. This study concludes that the development of sustainable transportation in the city of Surabaya has the potential to realise the concept of TOD as a medium for solving the problem of population density and congestion in the city of Surabaya